C‐C Motif Chemokine Receptor 9 Exacerbates Pressure Overload–Induced Cardiac Hypertrophy and Dysfunction. Issue 5 (May 2016) - Xu, Zhengxi; Mei, Fanghua; Liu, Hanning; Sun, Cheng; Zheng, Zhe
Abstract : Background: Maladaptive cardiac hypertrophy is a major risk factor for heart failure, which is the leading cause of death worldwide. C‐C motif chemokine receptor 9 (CCR9), a subfamily of the G protein–coupled receptor supergene family, has been highlighted as an immunologic regulator in the development and homing of immune cells and in immune‐related diseases. Recently, CCR9 was found to be involved in the pathogenesis of other diseases such as cardiovascular diseases; however, the effects that CCR9 exerts in cardiac hypertrophy remain elusive. Methods and Results: We observed significantly increased CCR9 protein levels in failing human hearts and in a mouse or cardiomyocyte hypertrophy model. In loss‐ and gain‐of‐function experiments, we found that pressure overload–induced hypertrophy was greatly attenuated by CCR9 deficiency in cardiac‐specific CCR9 knockout mice, whereas CCR9 overexpression in cardiac‐specific transgenic mice strikingly enhanced cardiac hypertrophy. The prohypertrophic effects of CCR9 were also tested in vitro, and a similar phenomenon was observed. Consequently, we identified a causal role for CCR9 in pathological cardiac hypertrophy. Mechanistically, we revealed a lack of difference in the expression levels of mitogen‐activated protein kinases between groups, whereas the phosphorylation of AKT/protein kinase B and downstream effectors significantly decreased in CCR9 knockout mice and increased in CCR9 transgenic mice after aortic binding surgery. Conclusions: The prohypertrophic effects of CCR9 were not attributable to the mitogen‐activated protein kinase signaling pathway but rather to the AKT–mammalian target of rapamycin–glycogen synthase kinase 3β signaling cascade.